Impact evaluation of invisible intimate partner violence on maternal healthcare utilization in Pakistan - Xinfang Xu; Di Liang; Saeed Anwar; Yanan Zhao; Jiayan Huang (BMC, 2024)
Abstract Introduction Existing research has shown that intimate partner violence (IPV) may hinder maternal access to healthcare services, thereby affecting maternal and child health. However, current studies have ignored whether emotional intimate partner violence (EV) could negatively affect maternal healthcare use. This study aims to evaluate the impact of invisible IPV on maternal healthcare utilization in Pakistan. Methods We analyzed nationally representative data from the Pakistan Demographic and Health Survey database from 2012-2013 and 2017-2018. Exposure to physical intimate partner violence (PV) and EV was the primary predictor. Based on women's last birth records, outcomes included three binary variables indicating whether women had inadequate antenatal care (ANC) visits, non-institutional delivery, and lack of postnatal health check-ups. A logistic regression model was established on weighted samples. Results Exposure to EV during pregnancy was significantly associated with having inadequate ANC visits (aOR = 2.16, 95% CI: 1.06 to 4.38, p = 0.033) and non-institutional delivery (aOR = 2.24, 95% CI: 1.41 to 3.57, p = 0.001). Lifetime exposure to EV was associated with increased risks of inadequate ANC visits (aOR = 1.48, 95% CI: 1.00 to 2.19, p = 0.049). Lifetime exposure to low-scale physical intimate partner violence (LSPV) (adjusted OR (aOR) = 1.73, 95% CI: 1.29 to 2.31, p < 0.001) was associated with increased risks of having no postnatal health check-ups. Conclusions Pregnant women who experienced EV and LSPV are at greater risk of missing maternal healthcare, even if the violence occurred before pregnancy. Therefore, in countries with high levels of IPV, early screening for invisible violence needs to be integrated into policy development, and healthcare providers need to be trained to identify EV and LSPV.